"Game over" for autonomous shuttles in mixed traffic? Results from field surveys among pedestrians and cyclists on how they interact with autonomous shuttles in real-life traffic in Norway. (March 2023) - Bjørnskau, Torkel; Aasvik, Ole; De Ceunynck, Tim; Fyhri, Aslak; Hagenzieker, Marjan; Johnsson, Carl; Laureshyn, Aliaksei
Highlights: Game theoretic basis for studying interaction between autonomous shuttles and ordinary road users in mixed traffic. Repeated field surveys in the two Norwegian cities with AV shuttle pilots. Pedestrians and cyclists are considerate and tend to yield to the AV shuttle at both sites. Cyclists in Oslo are less considerate towards the AV shuttle over time.